Analisa Motivasi Intrinsik dan Budaya Organisasi Terhadap Kinerja Perempuan Berkarir dengan Intervening locus of control internal di Bogor - Dinah, Dinah; Angka, Angka (www.bsi.ac.id, 2025)
Working in a company serves as a means of self-actualization for women and provides income for themselves and their families. However, a phenomenon has emerged where working women often exhibit a lack of performance in their fields, leading to suboptimal job execution. This presents a significant challenge for HR practitioners in companies to guide female employees to become more competent and skilled. The aim of this research is to analyze the influence of intrinsic motivation and organizational culture on the performance of career women, with internal locus of control as an intervening variable. This research uses a survey method with an explanatory research approach, which explains causal relationships between research variables through hypothesis testing. This is a quantitative study, focusing on intrinsic motivation (X1), organizational culture (X2), internal locus of control (Z), and the performance of career women (Y). The population of this study comprises all career women in the textile industry in Bogro, with a sample of 100 career women from PT.X.(SME) The research instrument is a questionnaire using a Likert scale, ranging from strongly disagree to strongly agree for responses. Statistical processing was assisted by SEM-PLS, and the R² value shows that intrinsic motivation, organizational culture, and internal locus of control influence the performance of career women by 90.6%, with the remaining 9.4% influenced by variables outside those studied.